Minimal differences in prevalence and spectrum of organic disease at upper gastrointestinal endoscopy between selected secondary care patients with symptoms of gastro-oesophageal reflux or dyspepsia. (3rd April 2017) - Irvine, Andrew J.; Pinto-Sanchez, Maria Ines; Bercik, Premysl; Moayyedi, Paul; Ford, Alexander C.
Abstract: Objectives: Gastro-oesophageal reflux and dyspepsia are felt to be separate upper gastrointestinal (GI) conditions. We aimed to measure the degree of overlap between them, and assess whether endoscopic findings differed. Material and methods: Demographic, symptom, upper GI endoscopy and histology data were collected from consecutive adults in secondary care. Patients were categorised according to whether they reported gastro-oesophageal reflux alone, dyspepsia alone or both, and patient demographics and endoscopic findings were compared. Results: Of 1167 patients, 97 (8.3%) had gastro-oesophageal reflux alone, 571 (48.9%) dyspepsia alone, and 499 (42.8%) overlap. Patients with overlap symptoms were more likely to smoke, compared with those with gastro-oesophageal reflux alone, or dyspepsia alone ( p = .009), but there were no other differences. Patients with gastro-oesophageal reflux alone or overlap had a higher prevalence of erosive oesophagitis (18.6% and 15.4% respectively, p < .001), but this was still the commonest diagnosis among those with dyspepsia alone (7.2%). No significant differences were seen in prevalence of other endoscopic findings. Conclusions: Gastro-oesophageal reflux and dyspepsia symptoms commonly overlap. There were minimal differences in demographics or spectrum of underlying organic disease between various symptom groups, suggesting that restrictive classifications according to predominant symptom may not be clinically useful.